III-Treatment of women in Ancient Rome: contribution of paleopathology to the reconstruction of violence. A case report (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: palaeopathology; trauma; Imperial Age; Rome